Pengaruh Keputusan Investasi, Keputusan Pendanaan, Kebijakan Dividen, dan Profitabilitas Terhadap Nilai Perusahaan (Studi pada Perusahaan Industri Dasar dan Kimia yang Terdaftar DI BEI Periode Tahun 2012-2016) - FAUZIAH, ANJIS; ASANDIMITRA HARYONO, NADIA (Jurnal Ilmu Manajemen (JIM), 2018)
Increasing the firm value is an important goal for a company to prosper its shareholders. The aim of this study is to examine the effect of the investment decision, financing decision, dividend policy, and profitability concerning to the firm value of the basic industry and chemical companies listed on the Indonesia Stock Exchange (IDX) 2012-2016 period. This research uses a causal research approach. The sample used is 49 companies with purposive sampling method. The analysis method used multiple linear regression analysis include classical asuumption test, and hypothesis test with SPSS version 22. The result of the regression analysis shows that investment decision, funding decision, and dividend policy have no effect on firm value. Profitability has significantly affects the firm value. This result shows that profitability is important to ben noticed by investors before buying shares on basic industry and chemical companies as a form of investment. Keywords: Firm Value, Investment Decision, Funding Decision, Dividend Policy, Profitability